Congenital Vascular Malformations of the Liver: An Association With Trisomy 21. Issue 6 (December 2016) - Burdall, Oliver C.; Grammatikopoulos, Tassos; Sellars, Maria; Hadzic, Nedim; Davenport, Mark
Abstract : ABSTRACT: A link between congenital vascular malformation (CVM) of the liver and trisomy 21 has been suggested. We reviewed all children with trisomy 21 referred for investigation to a specialist pediatric hepatobiliary unit (1985–2015). Forty-five children with trisomy 21 were identified; 7 (15%) had a defined CVMs (4 girls). All such infants were also diagnosed with a range of cardiac defects. CVMs were divided according to the nature of the vascular connection. Group (i) (n = 3): Abnormal venovenous anomaly. This included portocaval shunt and patent ductus venosus (n = 2). Group (ii) (n = 4): Involvement of all 3 vascular systems. Two infants had arterioportal hypertension caused by hepatic arteries feeding into a left portal vein aneurysm within the umbilical fissure. Two infants had more complex hepatic artery to hepatic vein shunts developing early cardiorespiratory failure with progressive jaundice. Our series shows a clear association between cardiac anomalies and CVM in children with trisomy 21.